2020
DOI: 10.3390/pharmaceutics12070636
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Study into Polymeric Materials in Low-Density Gastroretentive Formulations

Abstract: The extensive use of oral dosage forms for the treatment of diseases may be linked to deficient pharmacokinetic properties. In some cases the drug is barely soluble; in others, the rapid transit of the formulation through the gastrointestinal tract (GIT) makes it difficult to achieve therapeutic levels in the organism; moreover, some drugs must act locally due to a gastric pathology, but the time they remain in the stomach is short. The use of formulations capable of improving all these parameters, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 149 publications
(305 reference statements)
0
26
0
Order By: Relevance
“…For example, Föger and coworkers carried out some in vivo investigations to evaluate a novel oral formulation of PTX based on thiolated polycarbophil [156]. Polycarbophil is the USP/NF compendial name of a family of polyacrylic acids loosely crosslinked with divinyl glycol with broad applications in biomedical and pharmaceutical fields [157], including as a laxative to treat constipation. When thiolated, it was demonstrated that P-gp inhibition was enhanced significantly, thus reducing tumor growth in mammarycancer-induced rats more efficiently than intravenous paclitaxel [156].…”
Section: Thiomer-based Conjugates For Taxanes and Other Anticancer Api Administrationmentioning
confidence: 99%
“…For example, Föger and coworkers carried out some in vivo investigations to evaluate a novel oral formulation of PTX based on thiolated polycarbophil [156]. Polycarbophil is the USP/NF compendial name of a family of polyacrylic acids loosely crosslinked with divinyl glycol with broad applications in biomedical and pharmaceutical fields [157], including as a laxative to treat constipation. When thiolated, it was demonstrated that P-gp inhibition was enhanced significantly, thus reducing tumor growth in mammarycancer-induced rats more efficiently than intravenous paclitaxel [156].…”
Section: Thiomer-based Conjugates For Taxanes and Other Anticancer Api Administrationmentioning
confidence: 99%
“…The melt container had a size of 600 mL, but the capacity can be easily multiplied as needed. The vessel can be heated to 70°C, which makes it suitable for various moldable polymers and materials [26]. The main unit of foaming is the foam cell, where gas is dispersed in the molten dispersion with a high agitation speed.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the change in the swelling (Equation (3), Figure S3a) and matrix erosion Controlled-release gel-forming matrix tablets are known to undergo swelling and erosion during dissolution. A hydrophilic drug such as Met HCl penetrates and/or diffuses through the hydrated layer of HPMC K15M and is thus released in a controlled manner [68,69]. Erosion also plays an important role in releasing a drug, especially hydrophobic drugs, during dissolution [70].…”
Section: Floating Swelling and Erosion Testing Of The Sustained-release Non-effervescent Floating Tabletmentioning
confidence: 99%